Relational Sociological Analysis of Uncertainties: The case of COVID-19 In Turkey - Kasapoglu, Aytul; Akbal, Alev (Advances in Social Sciences Research Journal, 2020)
The main research problem of this study is that due to the uncertainties experienced, rationality has been replaced by feelings like morale panic and not all of the precautions will be applied by 55%, although it is known to be 90%. The main purpose of this article, Turkey and all experienced Covidien-19 (Corono virus)from the effects of a new virus in the world, is to examine the sociological basis of the news (reports) in the Turkish media The concepts of "uncertainties", "turning point" and "liminality" in social relations and values, classified by Harrison White (1992), constitute the theoretical basis of this relational sociological study. The research questions, in which the article was sought in the critical analysis of the media, were formed on the basis of this theoretical framework. Uncertainties in social relations and values have been tried to be revealed through political discourse analysis of pictures and messages (Van Dick, 2016). Research findings revealed that the news in the media related to COVID-19virus caused attitudes and behaviors similar to those observed in previous bird flue (2005) and pig flue (2010) outbreaks in Turkey. In other words, while ontological insecurities lead to irrational reactions (morale panic) with the contribution of the media, serious measures , such as curfews of people over 65, are not taken too seriously despite all warnings of the Minister of Health and Science Committee. On the other hand, it can be said that the authoritarian tendencies towards broader measures such as the curfew proclamation in the whole country have increased.